Education game / Azree Ramli - Ramli, Azree (2004)
The business of video games has become a billion dollar industry. For the past 3 decade, education games have become a vital part of our culture. Playing computer and video game can immerse people fantasy. Playing computer and games can build the mind of people from all sorts of ages. This is why educational game is important in our daily life. It can help the children to learn something new and to gain more knowledge. The main focus of this research is to find the fundamental of an education game. In addition, this research also focuses on finding the all the criteria in an education game. This research also will test all the criteria of education game with the online education game web.